Association between Herpes Simplex Type 1 Virus Infection and Bell’s Palsy - Islam, Mohammad Mohitul; Sarkar, Saumitra; Das, Priyatosh Chandra; Rahman, Touhidur; Sazib, S M Farhad (Bangladesh Journal of Neuroscience, 2016)
Background: Idiopathic facial paralysis is one of the commonest conditions in neurological practice. Objective: The purpose of this study is to see whether Bell’s palsy is associated with serological marker of Herpes Simplex virus type 1, and to study the clinical signs and symptoms manifested by Bell’s palsy. Methodology: This retrospective observational study was carried out in neurology OPD of ShSMCH, Dhaka from June, 2014 to May, 2016. All the patients who came to the OPD were selected as study population. All relevant data, those who fulfill the inclusion criteria were recorded in pre-designed data collection sheet. Result: A total number of 60 were recruited in this study. 30 were case group and 30 were control group. In our study, more than one quarter of cases (26.7%) was found between 26-30 years, while lowest age incidence was 16-20 years (6.7%). More than 37% of cases had their attack of Bell’s palsy in monsoon season, only 3% in autumn. 52.3% had pain in or around the ear. Taste abnormalities were found in 23.3%. Conclusion: From this study, it can be concluded that, Herpes simplex type 1 may be an important causative agent for Bell’s palsy. But a large scale study is needed for establishment of Herpes Simplex type 1 as an important infective agent for causation of Bell’s palsy. Bangladesh Journal of Neuroscience 2016; Vol. 32 (1): 12-15